The Influence of E-Commerce Utilization and Accounting Information Systems on the Performance of Micro, Small, and Medium Enterprises (MSMEs) - Sindi Kurnia; Itat Tatmimah; Muzayyanah (Universitas Muhammadiyah Makassar, 2025)
Digital transformation is increasingly essential for Micro, Small, and Medium Enterprises (MSMEs) to remain competitive in a dynamic business environment. This study aims to analyze the effect of e-commerce adoption and the implementation of accounting information systems (AIS) on MSME performance in Kuningan Regency. A quantitative explanatory research design was employed using purposive sampling, involving 35 MSME owners and managers as respondents. Data were collected through structured questionnaires and analyzed using multiple linear regression with a 5% significance level in SPSS (version XX). The results reveal that e-commerce adoption has a significant positive effect on MSME performance (β = 0.45, p < 0.05), particularly in market expansion, service efficiency, and customer engagement. Similarly, AIS implementation shows a significant positive effect (β = 0.41, p < 0.05), supporting better financial transparency and decision-making. The combined adoption of both technologies provides a substantial contribution to improving overall business performance (R² = 0.62). These findings highlight the importance of digital tools for enhancing MSME productivity, sustainability, and competitiveness, offering valuable insights for business owners and policymakers aiming to accelerate digital transformation initiatives.